(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2015)
This study examined the effect of explanatory captions of a multimedia summary on understanding the explanation of ozone depletion by primary school pupils. Participants were 54 eleven-year-old pupils of two share-sheltered primary schools in a medium-sized city in central Greece, who lacked adequate prior knowledge of ozone depletion, as they had not been systematically instructed about this phenomenon. Participants were randomly given one of the two versions of a printed material which concerned ozone depletion and were individually interviewed in an empty classroom. The first version of the printed material consisted of a main verbal text and a multimedia summary namely a concise, coherent and coordinated presentation of ozone depletion explanation using words and images- with explanatory captions. The second version was identical to the first, except that it did not include explanatory captions. Each student was invited to answer to 8 questions aiming at assessing their understanding of the explanation of ozone depletion. Participants who read the printed material with explanatory captions in the multimedia summary exhibited higher performance on understanding the explanation of ozone depletion than participants who read the printed material without explanatory captions. These results support the Cognitive Theory of Multimedia Learning, according to which educational material that promotes the connection between visual and verbal representations enhance understanding of scientific explanations. The findings may have implications in the design of science educational material.